C5a anaphylatoxin and its role in critical illness‐induced organ dysfunction. (15th October 2018) - Wood, Alexander J. T.; Vassallo, Arlette; Summers, Charlotte; Chilvers, Edwin R.; Conway‐Morris, Andrew
Abstract: Critical illness is an aetiologically and clinically heterogeneous syndrome that is characterised by organ failure and immune dysfunction. Mortality in critically ill patients is driven by inflammation‐associated organ damage and a profound vulnerability to nosocomial infection. Both factors are influenced by the activated complement protein C5a, released by unbridled activation of the complement system during critical illness. C5a exerts deleterious effects on organ systems directly and suppresses antimicrobial functions of key immune cells. Whilst several recent reports have added key knowledge of the cellular signalling pathways triggered by C5a, there remain a number of areas that are incompletely understood and therapeutic opportunities are still being evaluated. In this review, we summarise the cellular basis for C5a‐induced vulnerability to nosocomial infection and organ dysfunction. We focus on cells of the innate immune system, highlighting the major areas in need of further research and potential avenues for targeted therapies.